2017
DOI: 10.4172/2157-7110.1000680
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Functionality of Grape Pomace Used as a Nutritive Additive During Extrusion Process

Abstract: Grape pomace (GP) is a major byproduct of wine and juice industry, rich in polyphenolics with demonstrated health benefits. Extrusion processing for development of healthy and quality GP supplemented cornstarch snack foods was evaluated using response surface methodology. The retainability of polyphenolic content and antioxidant activity after extrusion processing were further assessed. The processing variables were feed moisture (16, 20, and 24 ± 0.2% w.b.), screw speed (150, 200, and 250 rpm), and the level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…For example, the hardness of corn-mango peel extrudates increased as the mango peel content exceeded 8% (Mazlan et al, 2019). Similar observations were reported in the studies of grape pomace, tomato pomace, and broccoli trimming (Altan et al, 2008a,b;Bisharat et al, 2013;Bibi et al, 2017). On the contrary, the amount of pineapple pomace added did not affect the hardness of extrudates (Selani et al, 2014).…”
Section: Hardnesssupporting
confidence: 79%
See 4 more Smart Citations
“…For example, the hardness of corn-mango peel extrudates increased as the mango peel content exceeded 8% (Mazlan et al, 2019). Similar observations were reported in the studies of grape pomace, tomato pomace, and broccoli trimming (Altan et al, 2008a,b;Bisharat et al, 2013;Bibi et al, 2017). On the contrary, the amount of pineapple pomace added did not affect the hardness of extrudates (Selani et al, 2014).…”
Section: Hardnesssupporting
confidence: 79%
“…High SDF, high sugar content, and low crystallinity index could be the reason for the highest expansion for apple pomace, among others. Another study with grape pomace also explained that high sugar content in grape pomace could be the reason for the increase in expansion ratio of extrudate with 5% of grape pomace, compared to the control (Bibi et al, 2017). In another study on apple pomace addition to regular and waxy cornstarch showed that extrudates with 15% inclusion of apple pomace had similar or even higher ER than the control in some conditions (Masli et al, 2018a).…”
Section: Expansion and Densitymentioning
confidence: 94%
See 3 more Smart Citations